Fuzzy sliding mode control of doubly-fed induction generator driven by wind turbine - Meriem Benmeziane; S. Zebirate; A. Chaker; Z. Boudjema (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper present a hybrid nonlinear control based on fuzzy sliding mode to control wind energy conversion system using a doubly fed induction generator (DFIG). Consiting of coupling fuzzy logic control and sliding mode control this technique is introduced to avoid the major disadvantage of variable structure systems, namely the chattering phenomenon. Effectiveness and feasibility of the proposed control strategy are verified by simulation results in Matlab Simulink.